How do we know we are measuring environmental attitude? Specific objectivity as the formal validation criterion for measures of latent attributes. (February 2018) - Kaiser, Florian G.; Merten, Martin; Wetzel, Eunike
Abstract: In this article, our aim is to introduce the formal validation criterion of specific objectivity to environmental psychologists. Using a convenience sample of 787 respondents, we constructed a set of attitude measures. We found that all five scales represented one attribute. As expected from the Campbell Paradigm, individual attitude can be inferred from verbal acts, such as expressions of appreciation, normative expectations, intentions to engage, and self-reports of past engagement in environmentally protective behaviors. Our findings challenge (a) the common practice in psychology of defining measures by their indicators and (b) the presumption of discriminant validity between typical measures of attitudes, subjective norms, perceived behavioral control, and intentions in research within the planned behavior framework. According to our research, the same validation criterion—specific objectivity—that is applied to the measurement of latent attributes in other empirical sciences (e.g., physics) can be applied to the measurement of attitudes. Highlights: Measures of latent attributes should not be defined by sets of indicator items. Specific objectivity is the core validation criterion for latent attribute measures. Empirical sciences—physics, psychology—depend on specifically objective measures. Environmental attitude is—within the Campbell Paradigm—objectively measurable. Typical measures used in planned behavior research assess a single latent attribute.